Efektivitas Penyusunan Rencana Strategis Pembangunan pada Badan Perencanaan dan Pembangunan Daerah Kabupaten Konawe - Crisbiantoro, Jefry (Jurnal Ilmiah Dikdaya, 2022)
The Effectiveness of Regional Development Strategic Plan Preparation for Development Planning in Konawe Regency and To find out what factors influence the effectiveness of developing a strategic development plan study at the Regional Development Planning Agency Office of Konawe Regency The data collection methods and techniques used in this study were library research and field studies while the data analysis technique used in this study is qualitative data analysis. The Regional Development Planning Agency (BAPPEDA) of Konawe Regency is a government agency that has the task of assisting the Regent in administering governance in the field of planning and controlling regional development, by carrying out the function of formulating technical policies. This research aims to determine the effectiveness of preparing development plans. budget preparation. This study uses descriptive qualitative methods. Data collection techniques are carried out through interviews, observation, and documentation. The results of this study indicate that the role of Bappeda Konawe Regency in preparing development planning is in accordance with the duties and functions as stipulated in the regulations. However, there are still a number of obstacles that have an impact on the less than optimal role of Bappeda itself in the process of determining the preparation of the development budget. First, the lack of preparedness of planning documents by the agencies during the process of discussing development programs and activities. Second, political factors in the regions that make programs and activities less effective and efficient. Third, the lack of supervision and control over the implementation of programs and activities that have an impact on not achieving the goals that have been set. To minimize these obstacles, the Konawe Regency Bappeda is trying to implement an electronic-based planning and budgeting system, taking preventive steps such as carrying out an action plan, which is a derivative of the master plan, in order to maximize and optimize the Special Autonomy Fund, to a strong commitment to review the departments agencies that do not complete planning documents and problematic projects. This is done so that programs and activities can be implemented in accordance with the rules and achieve the goals that have been set.